Patients with Atrial Fibrillation and Chronic Kidney Disease More Often Undergo Angioplasty of Left Main Coronary Artery - a 867 Patient Study - Anna Tomaszuk-Kazberuk; Dimitrios Nikas; Paulina Lopatowska; Elzbieta Młodawska; Jolanta Malyszko; Hanna Bachorzewska-Gajewska; Slawomir Dobrzycki; Bożena Sobkowicz; Ioannis Goudevenos (Karger Publishers, 2018)
Background/Aims: Several studies have implicated atrial fibrillation (AF) as a contributing factor in chronic kidney disease (CKD) and cardiovascular events. The prevalence of coronary artery disease (CAD) in patients with AF varies substantially from 17% to 46.5%. There are only few studies concerning renal function in population with AF undergoing coronary angiography. The aim of the present study was to assess which type of AF is dominant in CKD population scheduled for coronary angiography and if it can influence patients' outcome, the association between renal impairment and the type of coronary procedures in AF patients and the influence of renal function on in-hospital mortality. Methods: We retrospectively studied 867 patients with AF hospitalized due to coronary angiography in two year time. The cut off value of CKD was eGFR ≤ 60 ml/min./1.73m2 evaluated by CKD-EPI formula. Results: A total of 867 patients with AF (44% women; mean age 72±10 years) were included in the analysis. The mean eGFR was 44±11ml/min./1.73m2 in patients with CKD and 89±18 ml/min./1.73m2 in patients with preserved renal function. Patients with CKD and AF were older (p< 0.001), had more often diabetes (p=0.009), heart failure (p< 0.001) and anaemia (p< 0.001). Patients with CKD and AF had more often permanent type of AF (p< 0.001). In CKD patients CHA2DS2VASc score was 4.3±1.5 and HAS-BLED score was 2.0±1.2 and it was significantly higher as compared to population with preserved renal function (p< 0.001, p=0.02, respectively). The use of oral anticoagulation was less frequent in CKD group (p< 0.001) although these patients had higher CHA2DS2VASc score. Patients with AF and CKD were more often admitted due to myocardial infarction (STEMI or NSTEMI) (p=0.02, p< 0.001, respectively) and more often underwent percutaneous coronary intervention (PCI) (p=0.01). Among coronary arteries the percutaneous coronary intervention (PCI) of left main artery was done more frequently in CKD patients (p=0.01). Among CKD population in-hospital mortality was significantly higher in patients with eGFR < 30 ml/min (p< 0.001). Conclusion: Patients with CKD had more often permanent type of AF. Percutaneous interventions of the left main coronary artery, the only elective procedures influencing patients' prognosis, were done more frequently in CKD patients with AF. In-hospital mortality was significantly higher in patients with severe renal impairment. Despite the higher risk of ischaemic stroke in CKD group the use of oral anticoagulation therapy was significantly less frequent and the patients were deprived of the confirmed benefits of such treatment.